The Worse It Gets, The Better We Are - Joseph Marks (Journal of Applied Communications, 1986)
"It is the worst of times, it is the best of times." Sorry, Mr. Dickens, for the twist. But that's the way it is in the information business. The bad farm crisis has brought out the best in us.